The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00167-008-0531-0
|View full text |Cite
|
Sign up to set email alerts
|

Active non-operative treatment of acute isolated posterior cruciate ligament injury with cylinder cast immobilization

Abstract: The objective of our study was to investigate the outcome of an active non-operative treatment of the acute isolated posterior cruciate ligament (PCL) injury using cylinder cast immobilization and brace with tibial supporter. This study included 17 acute and isolated PCL injuries with two years or more of follow-up for each patient. We applied a cylinder cast immobilization with tibial supporter with full extension of the knee for 6 weeks, and then another 6 weeks of PCL brace with tibial supporter and posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 18 publications
0
54
0
Order By: Relevance
“…24,52 However, based on long-term follow-up studies, nonoperative treatment results in sustained instability, residual pain, cartilage degeneration, and additional meniscal injuries. 12,27 Interest in PCL reconstruction has increased, and surgical techniques have evolved with advances in arthroscopic instruments. However, the debate continues on the optimal technique, as a 20% to 60% frequency of osteoarthritis has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…24,52 However, based on long-term follow-up studies, nonoperative treatment results in sustained instability, residual pain, cartilage degeneration, and additional meniscal injuries. 12,27 Interest in PCL reconstruction has increased, and surgical techniques have evolved with advances in arthroscopic instruments. However, the debate continues on the optimal technique, as a 20% to 60% frequency of osteoarthritis has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies have suggested that isolated PCL injuries can be treated conservatively, resulting in favourable short-term clinical outcomes [1,15] Over the past few years, some evidences have emerged suggesting that the preservation of remnant of the ruptured cruciate ligament will improve the postoperative knee laxity and the recovery of proprioception [2,12]. In the present study, the tensioning of the remnant PCL and augmentation of the anterolateral bundle described by Jung et al [12] was used for contributing to posterior knee stability and proprioception.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of gravity is the largest risk factor in PCL graft elongation. In unsupported positions, gravity creates posterior tibial translation or "tibial sag," which increases the distance between the femoral and tibial attachment sites, straining the PCL graft and preventing healing at the correct length (Jung et al 2008). Attempts to limit tibial sag have included cylindrical casting in full extension (Jung et al 2008) and use of a knee immobilizer (Johnson 2009).…”
Section: Bracingmentioning
confidence: 99%
“…In unsupported positions, gravity creates posterior tibial translation or "tibial sag," which increases the distance between the femoral and tibial attachment sites, straining the PCL graft and preventing healing at the correct length (Jung et al 2008). Attempts to limit tibial sag have included cylindrical casting in full extension (Jung et al 2008) and use of a knee immobilizer (Johnson 2009). These techniques use additional padding on the posterior tibia to supply an anterior force, but they have not been evaluated for biomechanical efficacy (Jansson et al 2012).…”
Section: Bracingmentioning
confidence: 99%